Promoção de saúde e câncer de mama: um olhar a mais - Silva, Guilherme Ciribelli Fernandes da (2007)
According to bibliographical researches, little data were found related to patients who had had a discharging diagnosis, using the psychoanalytic approach, to find psychic factors that had helped patients to have this discharging diagnosis. The aim of this research is to identify, through the subject’s discourse, if psychic factors influenced the breast cancer treatment. The directing question was: Are there psychic factors that influence in the breast cancer treatment? This is a qualitative research that was carried out in a inner city of São Paulo State, and had two women, cured of breast cancer through conventional treatments with a multidisciplinary health team, participating in it. Semi-structured interviews with the two women were chosen as the instrument of the data collection. They were analyzed in the light of Discourse Analysis (DA) theories. The semi-structured interview (non-directive) was chosen aiming for listening the women, stimulating the free association of ideas but, at the same time, the researcher was able to enquire and deepen of some specific aspects. To find the subjects with the profile the researcher was looking for, it was very important the help of a multinational organization’s workers that, through meetings, gathered four women that had had breast cancer and then had a discharging diagnosis. The interviews were analysed in three stages, according to the discourse analysis’ model: 1st Stage: after some floating readings aiming for being imbued of them, there is an exhaustive contact with the material; 2nd Stage: data are cut and, afterwards, are joined together according to the content; 3rd Stage: finally, some interpretative hypothesis were formulated, based on psychoanalysis theories. Considering the importance that the psychoanalysis gives to the subject's singularity, it was essential in the study, because it led to an understanding of the history of each woman that participated in the research, enabling them to highlight the psychic factor that had helped them to have the discharge diagnosis, the desire of living. Finishing it is important to place that the psychic factor that had helped them to have I diagnosis it of high doctor, is the desire of living, this desire stimulated a change of the position of the citizen of the unconscious one of each one in relation to want to live. They had recognized this desire and had made the adhesion to the treatment to multidiscipline, also accepting the changes of habits necessary to continue alive and with quality of life.